Analisa kelengkapan resep narkotika dan psikotropika di rumah sakit x kota Depok - Nurwulan Adi Ismaya; Siti Novy Romlah; Diah Permata Sari; Nur Hasanah; Fajar Tri Kuncoroyekti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
The practice in prescribing and managing medicines: Narcotic and psychotropic drugsBackground: Using narcotic and psychotropic drugs in some hospitals now that have not implemented digital prescription. Nursing staff must be able to ensure that the prescription is legal and find some prescriptions written incomplete such as doctor name, date delivery without following the administrative standards and pharmaceutical requirements.Purpose: Analyze the feasibility of prescribing narcotics and psychotropics based on the completeness of administrative and pharmaceutical prescription requirements.Method: A Quantitative approach with descriptive analysis method. The recipes were analyzed based on; Administrative Completeness, Patient Administration, Pharmaceutical Completeness. A total of 750 narcotic prescriptions and 1378 psychotropic prescriptions were available at Puri Cinere Hospital from February to May 2020Results: Finding, 89.16% of narcotics prescriptions appropriate with the administrative requirements of the physician and 78.64% was appropriate with the administrative requirements of the patient and 99.76% was appropriate with the pharmaceutical requirements, while 89.18% of narcotics prescriptions were appropriate with the administrative and pharmaceutical requirements. As for psychotropic prescriptions, 90.70% of them were appropriate with the administrative requirements of the physician and 78.48% appropriate with the administrative requirements of the patient, 99.97% appropriate with the pharmaceutical requirements, while 89.78% of psychotropic prescriptions were appropriate with the administrative and pharmaceutical requirements.Conclusion: Approximately 100% of the prescriptions are in place where administrative requirements are appropriate. However, as far as pharmaceutical requirements are concerned, so many prescriptions still had no written a dosage in medicine.Keywords: The practice; Prescribing; Managing medicines; Narcotic; Psychotropic drugsPendahuluan: Penggunaan obat narkotik dan psikotropika di beberapa rumah sakit saat ini belum menerapkan resep digital. Staf perawat harus dapat memastikan bahwa resep tersebut legal dan menemukan beberapa resep yang tertulis tidak lengkap seperti nama dokter, tanggal pengiriman tanpa mengikuti standar administrasi dan persyaratan kefarmasian.Tujuan: Menganalisis kelayakan peresepan narkotika dan psikotropika berdasarkan kelengkapan persyaratan administrasi dan resep farmasi.Metode: Penelitian kuantitatif dengan metode analisis deskriptif. Resep-resep tersebut dianalisis berdasarkan; kelengkapan administrasi, administrasi pasien, kelengkapan kefarmasian. Sebanyak 750 resep narkotika dan 1378 resep psikotropika tersedia di RS Puri Cinere mulai Februari hingga Mei 2020.Hasil: Hasil dari penelitian ini adalah terdapat resep narkotika memenuhi 89,16 % persyaratan adminstratif dokter, 78,64% persyaratan administratif pasien dan 99,76% persyaratan farmasetik, secara keseluruhan memenuhi 89,16% memenuhi persyaratan administratif dan faramasetik dan untuk resep psikotropik memenuhi 90,70 % persyaratan adminstratif dokter, 78,48% persyaratan administratif pasien dan 99,97% persyaratan farmasetik, secara keseluruhan memenuhi 89,78% memenuhi persyaratan administratif dan farmasetik.Simpulan: berdasarkan kelengkapan administratif baik dari segi dokter maupun pasien baik untuk resep narkotik maupun psikotropik belum 100% lengkap. Berdasarkan kelengkapan farmasetik baik untuk resep narkotik dan psikotropik masih ada yang tidak menuliskan kekuatan obat / dosis obat.